The Kayu Aro Kerinci Tea Plantation Heritage as a Trace of Colonial History and a Source for Learning Local History in Jambi Province - Apdelmi; Alzadila Wahyuni (SINGOSARI, 2026)
This Kayu Aro Tea Plantation, located in Kerinci Regency, Jambi Province, is one of the oldest surviving Dutch colonial tea plantations that continues to operate today and possesses significant historical, social, economic, and cultural value. Nevertheless, its potential as a local history learning resource has not been optimally integrated into history education. This study aims to examine the historical values of the Kayu Aro Tea Plantation and explore its potential as a source of local history learning. The research employed a qualitative approach using historical research combined with library research. Data were collected through documentary studies of historical archives, scholarly literature, official documents, and other relevant secondary sources. Data analysis followed the stages of heuristics, source criticism, interpretation, and historiography, complemented by content analysis to identify the site's educational values. The findings reveal that the Kayu Aro Tea Plantation represents not only the development of the Dutch colonial plantation economy but also the social dynamics, labor migration, cultural acculturation, and societal transformation of the Kerinci community from the colonial era to the post-independence period. Historical remains, including the tea processing factory, Bedeng Delapan Hospital, administrators’ residences, and workers’ settlements, constitute authentic historical evidence that can serve as contextual learning resources. Integrating these heritage assets into history education enhances students’ historical thinking skills, strengthens cultural identity, fosters historical awareness, and supports the preservation of local cultural heritage. Therefore, the Kayu Aro Tea Plantation has substantial potential to be developed as a site-based history learning laboratory that promotes contextual, critical, and meaningful history education.